Evaluating responses of Caucasian apple (Malus orientalis) from Hyrcanian forests to fire blight (Erwinia amylovora) using an in vitro assay. Issue 6 (2nd November 2022) - Amirchakhmaghi, Narjes; Yousefzadeh, Hamed; Hosseinpour, Batool; Abdollahi, Hamid; Larsen, Bjarne
ABSTRACT: Fire blight, caused by the necrogenic gram-negative Erwinia amylovora, is one the most destructive bacterial diseases of apple. The wild Caucasian apple ( Malus orientalis ) is grown throughout Turkey, Armenia, Georgia, Russia and the Hyrcanian forest in the northern part of Iran. So far, no studies on resistance to fire blight in M. orientalis from the Hyrcanian forest have been conducted. We therefore evaluated the response of four different populations of M. orientalis (two individual trees per population) eight individuals of M. orientalis from four different populations in this region for fire blight resistance, using an in vitro shoot-inoculation assay. The fire blight susceptible MM.106 and partly resistant MM.111 rootstocks were included as references. Two one-year old trees were selected from each population, which were then micropropagated and inoculated with the fire blight bacterial strain 'Ea273ʹ. Necrosis growth along the shoots was measured every 24 h for 10 consecutive days. Selected individuals from Soordar, Asalem and Siahbil populations did not differ in the final necrosis growth from susceptible MM.106. However, the MM.111 and Afratakhteh individuals showed the lowest necrosis growth. The largest final necrosis growth was observed in the Siahbil individuals. The capacity of main scavenging enzymes and antioxidant activity were monitored in the Siahbil and the Afratakhteh individuals. The largest difference in the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) activity was observed at 72 hours post-inoculation (hpi) between resistant Afratakhteh and susceptible Siahbil individuals. The highest activity of catalase (CAT) enzyme occurred in the Afratakhteh individuals after 168 hpi. The peroxidase (POD) activity increased in both Afratakhteh and Siahbil individuals. The two Afratakhteh individuals were more resistant to fire blight compared to Asalem, Siahbil and Soordar individuals. Our results suggested that large differences in fire blight resistance existed in natural populations of M. orientalis . Potential fire blight-resistant individuals should be of interest for future apple-breeding programs.